Arbuscular mycorrhizal fungi decouple plant growth and vanadium accumulation by reprogramming vanadium dynamics in green foxtail (Setaria viridis) - Xi, Ze; Wang, Jinlong; Zhou, Yue; Dong, Yuexiao; Kinjal J., Shah; Zhang, Shujuan (Frontiers in Plant Science, 2026)
IntroductionThe urgent need for bioremediation strategies in vanadium(V)-polluted soils necessitates deeper insights into the role of arbuscular mycorrhizal fungi (AMF) in enhancing growth and V accumulation in green foxtail (Setaria viridis).MethodsUsing Rhizophagus irregularis as the tested AMF strain, we created two treatments under V stress (200 mg kg-1): inoculation with AMF and non-inoculation, to investigate how AMF colonization influences growth and V accumulation of green foxtail.ResultsWe found that under V stress, AMF inoculation increased leaf width by 27%, plant height by 60%, shoot biomass by 109% and root biomass by 104%. In addition, AMF decreased V concentrations across tissues: roots by 73%, chlorophyllous shoots by 74%, achlorophyllous shoots by 88%, and panicles by 94%. The biological enrichment factor was 0.4 for inoculated plants and 1.6 for non-inoculated plants while the translocation of V from roots to panicles and leaves was decreased by AMF inoculation. Subcellular analysis revealed preferential V sequestration in cell walls, accounting for 72% (inoculated) vs. 78% (non-inoculated) of total cellular V, with leaf cell wall concentrations being 34% lower in colonized plants. Additionally, AMF raised the levels of phytochelatins in roots by 8% and non-protein thiols by 31% and glutathione in both shoots (by 37% in leaves, 4% in stems) and roots (by 121%).DiscussionMore focus should be placed on AMF in the bioremediation of V-polluted soil as they decoupled plant growth and V accumulation by altering enrichment, translocation, subcellular distribution and chelation of V in green foxtail.